Detection of human bocavirus (HBoV) in children with acute respiratory infection (ARI) during the covid-19 transition period - Purnomosidi, Muhammad Abhi; Sjatha, Fithriyah; Yasmon, Andi (Sains Medika: Jurnal Kedokteran dan Kesehatan, 2023)
Acute respiratory infections (ARIs) are the highest cause of death in children in the world. Based on the 2018 Riset Kesehatan Dasar Nasional, ARI cases in Indonesia showed a prevalence of 4.4%, with the highest cases occurring in children. One of the new viruses first identified in 2005 in human nasopharyngeal samples is the human bocavirus (HBoV). HBoV is a single-strand DNA virus belonging to the Parvoviridae family. This study aimed to assess the prevalence of HBoV in children presenting with ARI during the transitional period of the Covid-19 era. HBoV detection was conducted using multiplex PCR and reverse hybridization methods on nasopharyngeal and oropharyngeal swab samples collected from symptomatic children. This study reported a prevalence rate of 4.94% for HBoV in 2022 and 5.04% in 2023. Furthermore, the study identified favorable detection rates for HBoV in children with ARIs as 14.81% in 2022 and 8.45% in 2023. These rates ranked 2nd and 5th highest among other pathogens detected in ARIs. Additionally, there was an increase in positive HBoV samples from 4 samples in 2022 to 6 samples in 2023, which was attributed to the relaxation of nonpharmaceutical Covid-19 interventions by mid-2022. HBoV was identified at a significant rate among children with ARI in Jakarta during the transitional phase of the Covid-19 era (2022-2023). Given its potential to induce severe ARI, HBoV necessitates heightened attention as an etiological agent.